Girl waits with gun - Stewart, Amy (Boston : Houghton Mifflin Harcourt, 2015)
Based on the forgotten true story of one of the nation's first female deputy sheriffs.
Keywords: Sheriffs -- New Jersey -- Paterson -- Fiction; Policewomen -- New Jersey -- Hackensack -- Fiction; Silk Workers' Strike, Paterson, N.J., 1913 -- Fiction; Black Hand (United States) -- History -- 20th century -- Fiction; Organized crime -- New Jersey -- Fiction; New Jersey -- History -- 20th century -- Fiction; Historical fiction